Pengenalan Hijuan Pakan Ternak Rumput Odot (Pennisetum purpureum cv. Mott) di Desa Ambalkumolo Kecamatan Buluspesantren - Muhammad Teguh; Saipul Sitohang; Adi Fathul Qohar; Efrilia Tri Wahyu Utami; Vian Dwi Chalisty; Nunur Nuraeni; Mugiarto Mugiarto (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Forage is the main food source needed by ruminants to survive, breed and produce. One type of superior grass that is often given to ruminants is dwarf elephant grass, because it has a high nutritional content and is palatable. The availability of quality and sustainable feed is one of the determining factors for the success of the livestock business. To increase the production of fodder forage, it is necessary to manage the cultivation of fodder forage, and the agricultural land used. The purpose of the Community Service activities (PKM) is to provide introduction, training and assistance to farmers or breeders, as well as education regarding quality feed processing management in terms of nutrition and quantity that can meet the basic livelihood needs, and livestock production and can be used for a long period of time. The results of community service activities need to be evaluated in fostering farmers to be more productive. The suggestions that can be given in the implementation of this community service program are that there needs to be a follow-up to the community service with improved facilities that are more supportive and a greater variety of feed plants, but must be accompanied by the provision of land for increasingly widespread feed quality in terms of nutrition and quantity.